A theory of national application of the European Convention on Human Rights - Bjorge, E (2014)
This study seeks to flesh out a theory of national application of the European Convention on Human Rights (ECHR). It does so by seeking to provide an answer to the research question, ‘what is the proper role of the domestic courts in the application of the European Convention?’ By relying upon the examples of French, German, and UK law, the study argues that it is not true in descriptive terms, nor desirable in normative terms, that the domestic courts take an approach to the ECHR based upon friction and assertion of sovereignty. This study argues instead that domestic application of the ECHR is built on the attainment of certain aims. These aims are inferred, in the main, from the domestic courts’ jurisprudence, such as it relates to four central ECHR doctrines, and they are: the doctrines of evolutionary interpretation; proportionality; the margin of appreciation; and autonomous concepts. On the basis of an analysis of this jurisprudence, the four aims are identified as being, first, honouring the principle of pacta sunt servanda; secondly, the safeguarding of human rights based upon the insight that human rights are a paramount good to be pursued; thirdly, the aim of positive, as opposed to negative, rights diversity; and, fourthly, the aim that conclusions reached on the domestic level of one state must be capable of being universalized. The approach of the domestic courts to the application of the ECHR can be explained on the basis of the domestic courts’ wish to attain these four aims. The proper role played by the domestic courts, the study argues, is one in which they are willing to give a lead to Strasbourg as well as to be led, in both, to use the wording of the Preamble of the ECHR, ‘the maintenance’ and in the ‘further realisation’ of the Convention rights.